PENGARUH EDUKASI KESEHATAN TERHADAP PERILAKU IBU DALAM PENCEGAHAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS SENTOSA BARU MEDAN - Saragih, Sri Rolastri; Silaen, Harsudianto Silaen (Excellent Midwifery Journal, 2024)
Background: Several types of complaints are felt by children with diarrhea, one of which is when defecation is more frequent and the stool is more watery than usual or a state of abnormal stool excretion, this is characterized by an increase in volume, wateriness, and frequency of bowel movements > 3 times a day and can be seen in toddlers if the frequency of urinating is more than 4 times a day with or without mucus and blood, it can be called diarrhea. Purpose: To determine the frequency distribution of mothers' knowledge at the Sentosa Baru Health Center in Medan Method: The type of design used in this research is quantitative, with the research design using the Quasi Experimental method with a one group pre-test and post test approach. In this design, there is also no comparison group (control). Results: The results of this study indicate that there is an influence of maternal behavior in preventing diarrhea in toddlers. The pre-test and post-test that have been carried out by the Wilcoxon signed test give significant results where the effect of health education on diarrhea prevention in the working area of the Sentosa Baru Medan Health Center is indicated by the value p=0.005 is smaller than (0.05). Conclusion: There is an influence before and after health education on maternal behavior.